2018
DOI: 10.1371/journal.pone.0193582
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell maculopathy: Identification of systemic risk factors, and microstructural analysis of individual retinal layers of the macula

Abstract: PurposeTo identify systemic risk factors for sickle cell maculopathy, and to analyze the microstructure of the macula of Sickle Cell Disease (SCD) patients by using automated segmentation of individual retinal layers.MethodsThirty consecutive patients with SCD and 30 matched controls underwent spectral-domain optical coherence tomography (SD-OCT) and automated thickness measurement for each retinal layer; thicknesses for SCD patients were then compared to normal controls. Demographic data, systemic data, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
2
22
1
Order By: Relevance
“…It has been shown that low fetal hemoglobin level could increase the risk for sickle cell patients to develop sickle retinopathy [7,8]. However, in contrast to Dell' Arti et al, we found no link between fetal hemoglobin expression level and the presence of maculopathy or retinopathy [9]. This finding could be related to the small number of patients included in our study.…”
Section: Dear Editorcontrasting
confidence: 99%
“…It has been shown that low fetal hemoglobin level could increase the risk for sickle cell patients to develop sickle retinopathy [7,8]. However, in contrast to Dell' Arti et al, we found no link between fetal hemoglobin expression level and the presence of maculopathy or retinopathy [9]. This finding could be related to the small number of patients included in our study.…”
Section: Dear Editorcontrasting
confidence: 99%
“…In a paediatric population, Martin et al [12]found no association with increasing age, gender, or genotype. In adults with sickle cell disease, Dell’Arti et al [9] reported no association between SCM and age, gender, or genotype; in contrast, Mathew et al [8] reported positive associations with both younger age and HbSS genotype. Others have also reported an association with the HbSS genotype [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al recently showed that macular thinning in SCD is associated with age, retinopathy, and HbSS genotype 11. Furthermore, another recent study suggested that high HbF levels and chelation therapy are possible protective factors for the presence of sickle cell maculopathy 12…”
Section: Introductionmentioning
confidence: 99%